2017
DOI: 10.1093/ckj/sfx132
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes of fluoroscopic and ultrasound-guided placement versus laparoscopic placement of peritoneal dialysis catheters

Abstract: BackgroundSeveral peritoneal dialysis catheter (PDC) placement techniques have been described. The objective of this study was to compare the fluoroscopy and ultrasound guidance technique with the laparoscopic technique.MethodsWe retrospectively reviewed the medical records of 260 patients who had their first PDC placed between January 2005 and June 2016. We compared the outcomes of the fluoroscopic and ultrasound-guided catheter placement technique (radiologic group, n = 50) with the laparoscopic catheter pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
(19 reference statements)
0
13
0
Order By: Relevance
“…In contrast, retrospective studies have reported incidences of 20.2% using blind percutaneous insertion and 27.1% using laparoscopy 20,21 . In some reports, incision and tunnel infection have occurred regardless of technique (surgical laparotomy, percutaneous puncture, or laparoscopic catheterization) 5,20,22 . We believe that our new PD catheterization method has inherent advantages in this regard.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, retrospective studies have reported incidences of 20.2% using blind percutaneous insertion and 27.1% using laparoscopy 20,21 . In some reports, incision and tunnel infection have occurred regardless of technique (surgical laparotomy, percutaneous puncture, or laparoscopic catheterization) 5,20,22 . We believe that our new PD catheterization method has inherent advantages in this regard.…”
Section: Discussionmentioning
confidence: 84%
“…Of the 20 studies, most (9 studies) [1, 4, 5, 19, 31-35] compared the blind percutaneous insertion technique with open surgery, 1 [36] compared percutaneous techniques utilizing radioscopic guidance or not with open surgery and reported respective outcomes. Three studies [37-39] compared the blind percutaneous method with laparoscopy, 1 study [40] compared the blind percutaneous technique with open surgery or laparoscopy, 1 study [41] compared the guided percutaneous method with open surgery, 4 studies [18, 20, 42, 43] compared the guided percutaneous method with laparoscopy, and 1 study [44] compared the guided percutaneous technique with open surgery or laparoscopy. Overall, the pooled data included 3,626 PD catheter insertions, with 1,826 percutaneous procedures and 1,800 surgical procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 98 articles, 48 of them did not meet the inclusion criteria and were excluded after reading the full text. Finally, 41 eligible papers were included, 18 58 namely, 9 RCTs 18 –26 and 32 observational clinical studies. 27 …”
Section: Resultsmentioning
confidence: 99%
“…Finally, 41 eligible papers were included, 18 58 namely, 9 RCTs 18 –26 and 32 observational clinical studies. 27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation